Bilateral Synchronous Stress Fracture of the Tibia in a Young Female Basketball Player. Issue 1 (16th May 2016) - Posadzy, Magdalena; Vanhoenacker, Filip
We present a case of a bilateral synchronous stress fracture of the tibia in a young female basketball player. The patient was initially referred for ultrasound and radiographs of the knees to exclude Osgood-Schlatter disease. Radiographs and subsequent MRI revealed bilateral stress fractures of the proximal tibia. A synchronous and symmetrical occurrence of stress fractures in the lower limbs is unusual. As clinical presentation is often nonspecific, appropriate imaging (plain films and MRI) plays a pivotal role in the correct diagnosis of this uncommon entity.